The Effects of Firm Size on Job Quality: A Comparative Study for Britain and France - Alex Bryson; Christine Erhel; Zinaïda Salibekyan (Institute of Labor Economics (IZA), 2017)
Using linked employer-employee data from two comparable surveys this article examines the links between non-pecuniary job quality and workplace characteristics in Britain and France countries with very different employment regimes. The results show that job quality is better in Britain than it is in France, despite its minimalist regulatory regime. The difference is apparent for all dimensions of job quality (skill development, training participation, job autonomy, job insecurity, work-life balance and relations between employers and employees), except skills' match to a job. Firm size is negatively associated with non-pecuniary job quality in both countries but in France the association is confined to only the largest firms. Internal Labour Markets (ILMs) are associated with higher job quality in France, but not in Britain.
Keywords: I31; J30; J81; 330; job quality; firm size; internal labour market; comparative; linked employer-employee data; Britain; France